Effects of Placenta-Derived Mesenchymal Stem Cells on the Particulate Matter-Induced Damages in Human Middle Ear Epithelial Cells - So Young Kim; Seung Ha Oh; Jun Ho Lee; Myung-Whan Suh; Moo Kyun Park (Hindawi Limited, 2019)
This study was aimed at investigating the effects of placenta-derived mesenchymal stem cells (PL-MSCs) on particulate matter- (PM-) exposed human middle ear epithelial cells (HMEECs). HMEECs were treated with 300 μg/ml PM for 24 hours. The PL-MSCs were cocultured with PM-treated HMEECs. Cells were harvested on days 0, 1, and 4, and the expression of the inflammatory genes TNFα, COX2, IL1β, IL6, and MUC5B in HMEECs and anti-inflammatory genes PTGES, TGFβ, and VEGF in PL-MSCs was examined by qRT-PCR. The culture media were collected to measure the secreted PGE2 level using an enzyme-linked immunosorbent assay. The mRNA expression of TNFα, COX2, IL1β, IL6, and MUC5B in HMEECs increased following PM treatment. PM-treated HMEECs cocultured with PL-MSCs showed alleviated inflammatory reactions represented by lower mRNA expression levels of MUC5B, TNFα, IL1β, and IL6 compared to monocultured PM-treated HMEECs. The mRNA expression levels of PGE2, TGFβ, and VEGF were elevated in cocultured PL-MSCs compared to those of control PL-MSCs. The medium of PM-treated HMEECs cocultured with PL-MSCs exhibited increased PGE2 levels. The increased inflammatory response in PM-treated HMEECs was reversed using PL-MSCs. The PGE2, TGFβ, and VEGF were the mediators of the anti-inflammatory effects of PL-MSCs.